2018
DOI: 10.3390/tropicalmed3030103
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and Deaths Associated with Diarrhea and Respiratory Diseases among Children Aged 0–5 Years in a Referral Hospital of Mauritania

Abstract: Diarrhea and respiratory diseases are the leading causes of morbidity and mortality among <5-year-olds worldwide, but systematic data are not available from Mauritania. We conducted a hospital-based retrospective study. Data on admissions to Mauritania’s National Referral Hospital (the main pediatric referral center in the country), due to diarrhea and respiratory diseases, during 2011–2014, were analyzed. A total of 3695 children <5 years were hospitalized during this period; 665 (18.0%) due to respiratory di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…The case fatality rate of 4.9% in our study was lower compared to studies from Malawi and Nigeria, both showing rates of about 10% [ 20 , 21 ], and was much lower than the rates reported for hospitalised children in Mauritania (18%) [ 22 ]. Conversely, lower case fatality rates were reported in South Africa (2%) [ 23 ].…”
Section: Discussioncontrasting
confidence: 89%
“…The case fatality rate of 4.9% in our study was lower compared to studies from Malawi and Nigeria, both showing rates of about 10% [ 20 , 21 ], and was much lower than the rates reported for hospitalised children in Mauritania (18%) [ 22 ]. Conversely, lower case fatality rates were reported in South Africa (2%) [ 23 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Babylon City study 33 and with the study. 42 Group of 7-12 months. 31 others 29 Disagree with the study showed that half of the children were below 6 months of age, 37% in the age group of 7-12 months.…”
Section: Rapid Test Resultsmentioning
confidence: 99%
“…Interestingly, different studies have reported different sex-specific patterns for specific diseases. A study from Mauritania in children <5 years with diarrhea and respiratory diseases 32 found higher risk for diarrhea-associated deaths among females while respiratory disease-associated deaths were more common in males. The patterns for injuries is more consistent: several studies have shown that the proportion of injured pediatric patients is higher in males than in females.…”
Section: Discussionmentioning
confidence: 99%